Differential fold interference patterns in an intracontinental orogen: Insights from superposed buckle folding in southern Jiangxi Province, South China Block - Li, Chunlin; Wang, Zongxiu; Tan, Yuanlong; Li, Leilei (Journal of structural geology, 2023)
The South China Block (SCB) experienced multi-stage tectono-magmatic events during the Mesozoic, forming a broad and episodic intracontinental orogenic belt. It is controversial whether the driving force of the Mesozoic intracontinental orogeny in the SCB is related to the far-field effects of plate convergence. To better understand the driving mechanism of intracontinental orogeny, we conducted a detailed structural investigation of the Xingguo area in southern Jiangxi Province, located in the central part of the SCB. Two regional-scale buckling superposed folds were identified as the Chayuan arcuate syncline of the fold axis protruding to the north (Type 2a interference pattern) and the Xiefang syncline of the fold axis extending NW–SE (Type 1d interference pattern). Although there are differences in fold interference patterns, the Chayuan arcuate syncline and Xiefang syncline were formed by the superimposition of the Middle–Late Triassic NE–SW shortening and the Middle–Late Jurassic nearly E–W shortening. This phenomenon of the differential fold interference patterns in the same tectonic setting is determined by the difference in geometric characteristics of their initial folds. Combined with the variation of the Mesozoic paleostress field, it is considered that the Mesozoic intracontinental orogeny in the SCB is mainly controlled by the far-field stress propagation generated by plate interactions. Based on the analysis of tectonic architecture, we propose that the Mesozoic tectonic evolution of the SCB experienced a transformation from multi-plate convergence in the Triassic to Andean-type subduction in the Jurassic. This tectonic transformation finally resulted in the reactivation of the Precambrian multi-terrane collage of the SCB. •Regional-scale superposed folds in the interior of the South China Block (SCB) are investigated.•Two buckling superposed folds are identified as the Chayuan arcuate syncline (Type 2a interference) and the Xiefang syncline (Type 1d interference).•Differential fold interference patterns result from two shortening events with different directions.•The SCB experienced a transformation from multi-plate convergence in the Triassic to Andean-type subduction in the Jurassic.•Far-field effects of plate convergence control the Mesozoic intracontinental orogeny of the SCB.